2015
DOI: 10.1002/sdtp.10480
|View full text |Cite
|
Sign up to set email alerts
|

22.1: Invited Paper: New Fluorescent Blue Host Materials for Achieving Low Voltage in OLEDs

Abstract: New fluorescence blue host (BH) materials for achieving low voltage have been developed. Low efficiency and short lifetime were main issues to reduce operation voltage when using former generation blue hosts. Therefore new molecular structure of BH was designed to improve both electron and hole mobility and optimize ionization potential (IP) for overcoming the issues. New BHs showed lower voltage and comparable lifetime than former generation BHs. Furthermore, as a result of device optimization using the new B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In order to enhance TTF efficiently, it is important to generate excitons locally to increase the exciton density. However, the previous studies have shown that excess carriers quench the localized triplet excitons and inhibit TTF 9,19 . It was also considered that locally increased high exciton density had an adverse effect on the device lifetime.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to enhance TTF efficiently, it is important to generate excitons locally to increase the exciton density. However, the previous studies have shown that excess carriers quench the localized triplet excitons and inhibit TTF 9,19 . It was also considered that locally increased high exciton density had an adverse effect on the device lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…However, the previous studies have shown that excess carriers quench the localized triplet excitons and inhibit TTF. 9,19 It was also considered that locally increased high exciton density had an adverse effect on the device lifetime.…”
Section: Concept Of Bilayer Emlmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to enhance TTF efficiently, it is important to generate excitons locally to increase the exciton density. However, the previous studies have shown that excess carriers quench the localized triplet excitons and inhibit TTF [5], [6]. It was also considered that locally increased high exciton density had an adverse effect on the device lifetime.…”
Section: -1 Concept Of Bilayer Emlmentioning
confidence: 99%